Ottoman Turkish State Practices - Imam Mulia Tua Harahap; Cintami Grece Novita Ramadani (AT-TAFAHUM: Journal of Law, 2024)
This study examines the constitutional system of the Ottoman Empire as a model of government in Islamic history that exerted widespread influence and endured for more than six centuries. This study aims to examine the government structure, factors of progress, and the roots of the decline of the sultanate through a qualitative approach based on library research utilizing various sources of books and scientific journals. The results of the study indicate that the constitutional system of the Ottoman Empire was unique in that it united political and religious authority under one leadership figure, namely the sultan who also served as caliph. The glory of this sultanate was supported by several main pillars, including a solid bureaucracy, effective economic management, and progress in education and science. However, this sultanate ultimately experienced decline triggered by internal factors in the form of prolonged conflict and declining moral values, as well as external factors in the form of geopolitical pressure from the ever-increasing Western powers. It was the accumulation of these various pressures that then drove the transformation towards a secular state, and at the same time marked the end of the Ottoman Caliphate in the history of Islamic civilization.